Revolutionising Education: The Role of SCT-Based E-Modules in Fostering Creative Thinking - Rusmansyah Rusmansyah; Rizqi Noor Hayati; Mahdian Mahdian; Parham Saadi; Isnawati Isnawati; Arief Ertha Kusuma; Asih Widi Wisudawati (JINoP (Jurnal Inovasi Pembelajaran), 2025)
Creative thinking is crucial for students in addressing educational and daily challenges. It enables them to analyze problems and generate innovative solutions. The SCT-based e-module supports this development by allowing students to manage learning independently, thereby enhancing comprehension and creative thinking. This study employs a Research and Development (R&D) approach, utilizing the 4D model: Define, Design, Develop, and Disseminate. The aim is to create a valid, practical, and effective SCT-based e-module on buffer solutions. Conducted at SMAN 1 Martapura, the study involved five students in individual trials, 10 in small group trials, and 35 in limited trials. Data analysis showed: (1) Validity reached 84.89%, categorized as highly valid; (2) Practicality was confirmed by student responses (83% in individual trials, 83.5% in small groups) and teacher responses (92.5%), indicating high practicality; (3) Effectiveness was measured through students' creative thinking N-gain scores, which averaged 0.54, signifying moderate effectiveness. These results confirm the SCT-based e-module as an effective tool for fostering students' creative thinking.